1990
DOI: 10.1007/bf02555915
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP-dependent membrane protein phosphorylation and calmodulin binding are involved in the rapid stimulation of muscle calcium uptake by 1,25-dihydroxyvitamin D3

Abstract: Rapid in vivo effects of 1,25-dihydroxyvitamin D3 on muscle calcium metabolism have been reported. In vitro studies have shown that exposure of vitamin D-deficient chick soleus muscles to the sterol for 1-10 minutes causes a significant stimulation of tissue 45Ca uptake which can be suppressed by Ca channel blockers. A parallel increase in muscle membrane calmodulin content that could be mimicked by forskolin was observed. Experiments were carried out to obtain information about the mechanism underlying the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

1991
1991
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 22 publications
2
10
0
2
Order By: Relevance
“…Receptors for 1,25(OH)2D3 and functional responsiveness to 1,25(OH)2D3 at physiological hormone concentrations have been demonstrated in cultured human muscle cells [27,28]. Various lines of evidence suggest a role of 1,25(OH)2D3 in the regulation of intracellular calcium fluxes and the synthesis of the actomyosin contractile complex, therefore affecting the contraction-relaxation cycle [15,29,30]. Similarly, receptors for IGF-I have been identified in human muscle tissue [16] and IGF-I has been shown to promote the synthesis of different muscle protein components [16,31].…”
Section: Discussionmentioning
confidence: 99%
“…Receptors for 1,25(OH)2D3 and functional responsiveness to 1,25(OH)2D3 at physiological hormone concentrations have been demonstrated in cultured human muscle cells [27,28]. Various lines of evidence suggest a role of 1,25(OH)2D3 in the regulation of intracellular calcium fluxes and the synthesis of the actomyosin contractile complex, therefore affecting the contraction-relaxation cycle [15,29,30]. Similarly, receptors for IGF-I have been identified in human muscle tissue [16] and IGF-I has been shown to promote the synthesis of different muscle protein components [16,31].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that the rapid stimulation of Ca 2ϩ influx by 1␣,25(OH) 2 D 3 in various cells was abolished by specific inhibitors of adenylate cyclase and PKA (113,282,498). In vitamin D-deficient chick soleus muscles, 1␣,25(OH) 2 D 3 (10 pM to 10 nM) elevated tissue cAMP levels within 45 s to 5 min and increased adenylate cyclase activity (150). Similarly, intracellular cAMP levels rose in chick cardiac muscle and rat enterocytes after stimulation with 1␣,25(OH) 2 D 3 (283,434).…”
Section: G Vitamin Dmentioning
confidence: 99%
“…In previous studies it was shown that the rapid changes in 45 Ca 2ϩ influx induced by 1,25-(OH) 2 D 3 in both intact soleus muscle and cultured myoblasts are paralleled by an increase in the amounts of calmodulin (CAM) bound to membranes at the expense of a decrease in its cytosolic concentration without any change in total CAM cellular content (13,14). There is a diversity of cellular responses controlled by Ca 2ϩ -dependent pathways utilizing CAM as the signaling mediator (15), the activation and/or modulation of which occurs either through direct interaction with target proteins or via CAM-dependent activation of regulatory proteins (16).…”
mentioning
confidence: 99%